Note on a Cloth of Estate traditionally said to have been worked by Mary Queen of Scots and her Ladies when in England - Stewart, W Balfour (Proceedings of the Society of Antiquaries of Scotland, 1918)
This cloth of estate, which is traditionally said to have been worked by Mary Queen of Scots and her ladies, is the property of Miss Power, who succeeded to it through her ancestors the Jermyns of Rushbrooke Hall, Suffolk. The cloth has been in possession of the Jermyn family for several generations, but how they became possessed of it is not known, nor is there any history of it prior to that time. It has unfortunately been 'restored'. In the inventory of the effects of Mary of Guise handed over to her daughter, Mary Queen of Scots, in November 1561, there is a description of a cloth of estate which is very similar.